CASE STUDY OF THE GRADE A CONSTRUCTION COMPANY ON OPERATIONAL DIFFICULTIES IN TAIWAN - Chen, Tung-Fa; Lu, Te-Tsai (International Journal of Application on Economics and Business, 2024)
The construction industry plays a crucial role in the national economic development. Despite the Taiwan government investment substantial in various infrastructure, the operational challenges faced by the construction industry still severe, especially for “Grade A” construction companies. The study encompasses five major dimensions: industry policies and regulations, human resources, financial management, cost of raw material, and subcontracting management systems. Qualitative research methods are employed, including in-depth interviews with experts from the industry, government, and professional technicians. The suggestions gathered from these interviews are further refined through focus group discussions. This study concludes with recommendations for government agencies, the national tax authority, design and supervision entities, construction companies, and specialized subcontractors within the construction industry.